REmaking L.A. into the New City with Big Shoulders - Elizabeth Martin (Oz, 1996)
Great streets often form the vibrant edge of two distinct neighborhoods. Streets, especially wide arterials, need simple broad-stroke design solutions, rather than overly detailed ideas that are lost on moving motorists.